Electron Beam Irradiation‐Induced Formation of Defect‐Rich Zeolites under Ambient Condition within Minutes. Issue 27 (1st June 2021) - Chen, Junchang; Zhang, Mingxing; Shu, Jie; Yuan, Mengjia; Yan, Wenfu; Bai, Pu; He, Linwei; Shen, Nannan; Gong, Shicheng; Zhang, Duo; Li, Jiong; Hu, Jiangtao; et al.
Abstract: Zeolites are a well‐known family of microporous aluminosilicate crystals with a wide range of applications. Their industrial synthetic method under hydrothermal condition requires elevated temperature and long crystallization time and is therefore quite energy‐consuming. Herein, we utilize high‐energy electron beam irradiation generated by an industrial accelerator as a distinct type of energy source to activate the formation reaction of Na‐A zeolite. The initial efforts afford an attractive reaction process that can be achieved under ambient conditions and completed within minutes with almost quantitative yield, leading to notable energy saving of one order of magnitude compared to the hydrothermal reaction. More importantly, electron beam irradiation simultaneously exhibits an etching effect during the formation of zeolite generating a series of crystal defects and additional pore windows that can be controlled by irradiation dose. These observations give rise to significantly enhanced surface area and heavy metal removal capabilities in comparison with Na‐A zeolite synthesized hydrothermally. Finally, we show that this method can be applied to many other types of zeolites. Abstract : Defect‐rich Na‐A zeolites were synthesized by electron beam irradiation under ambient condition within minutes. The as‐synthesized Na‐A shows enhanced adsorption performance for CO2 and heavy ions in comparison with samples synthesized hydrothermally.